Pelaksanaan Kegiatan Pengabdian Masyarakat Webinar Nasional Building Bright Future for Generation Z bagi Siswa-Siswi SMA Jabodetabek - Prasetya, Wibawa; TIUAJ, yanto; Surbakti, Feliks Prasepta (Jurnal Pengabdian Masyarakat Charitas, 2023)
The objective of this community service activity is to celebrate national “95th youth pledge day” as well as to provide knowledge and basic skills for Generation Z about digital ability in this digital era. This activity was a collaboration between Industrial Engineering Department with Marketing Agencies of Atma Jaya Catholic University of Indonesia. There were four speakers in this webinar who presented various topics related to the knowledge and skills needed in the digital era and how young Generation Z should adapt with the situation so that they could benefit and success in the future. After the presentation from the speakers were delivered, the participants could ask the questions regarding the topics. In this conference, more than 100 participants from various schools in Greater Jakarta and parents participated online via zoom. In addition, the event could also be watched via youtube channel.